HUBUNGAN SENAM JANTUNG SEHAT DENGAN TINGKAT STRES PADA LANSIA DI KELOMPOK SENAM JANTUNG SEHAT AMONG ROSO KECAMATAN NGLUWAR KABUPATEN MAGELANG - Nugroho, Eko Setyawan; Suhariyanti, Enik; Kamal, Sodiq (Journal of Holistic Nursing Science, 2016)
The situation is causing the elderly experience different kinds of stress one of which is the psychological stress, psychological stress is a set of physiological changes as a result of the body exposed to the danger of the threat. This stress can affect the physical and psychological affects the elderly. One is a healthy heart gymnastics, Gymnastics Healthy Heart is a sport that is prepared with always put the ability of the heart, the movement of large muscle and joint flexibility, as well as attempts to include as much oxygen as possible. The purpose of this study to determine the relationship healthy heart gymnastics with Stress Levels in the Elderly in Group Gymnastics Heart Healthy Heart Among Roso Ngluwar District of Magelang regency. The method used was a cross sectional, with a sample of 57 elderly. The instrument used was a questionnaire heart gymnastics and stress levels. Data processed by Spearman rank test. The result showed a p-value 0,000 < = 0.05, which means that therea is a relationship between a healthy heart gymnastics with the level of stress in Group Gymnastics Heart Healthy Heart Among Roso Ngluwar District of Magelang regency.